Digital Marketing Innovation for MSMEs through ChatGPT Integration and Management Information Systems: A Technological Transformation Approach for Competitive Advantage - Susilowati Ningsih; Budi Tjahjono (Politeknik Ganesha Medan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia's economy. However, with technological advancements and changing consumer trends, MSMEs face substantial challenges in maintaining and enhancing their competitiveness. The development of digital technology is an imperative that cannot be ignored if MSMEs are to remain relevant and competitive in the modern era. This research examines how the integration of ChatGPT and Management Information Systems (MIS) can positively impact the digital marketing of MSMEs and how these enterprises can leverage this technology to enhance their competitiveness. This study employs a literature review method with a qualitative approach. Data were obtained from Google Scholar covering the period from 2014 to 2024. The results indicate that digitalization, through the implementation of technologies such as ChatGPT and Management Information Systems, significantly impacts MSMEs by enhancing their competitiveness. Integrating ChatGPT with MIS not only improves operational efficiency but also enriches customer experience through more responsive and personalized services. Case studies from companies like Tokopedia, Zalora, and Kopi Kenangan demonstrate that adopting digital technology can expand market reach, increase sales, and improve stock management. However, challenges such as infrastructure limitations and the need for staff training must be addressed to ensure successful technology adoption. The long-term success of digital technology highlights the importance of sustainable investment and adaptation to evolving market trends.